The heinemann science scheme. book 3 - Bradley, Ian; Gale, Peter Winterbottom, Mark (Heinemann Oxford, 2002)
The "Heinemann Science Scheme" offers an approach to the QCA's Scheme of Work. Teacher's resource packs provide support with lesson planning, with each chapter matching the Scheme of Work, and in-built assessment.